Perceptions of Physics Students on the Importance of Physics in Sports - Primadi, Muhamad Baidhowi; Nugraha, Afif Dwi (MACCA : Science-Edu Journal, 2024)
This study aims to identify and analyze the perceptions of physics students about the relevance of physics in sports. Although physics is often considered a theoretical discipline, many physics principles underpin various techniques and movements in sports, such as Newton's laws of motion, energy principles, and momentum. However, students' understanding of these correlations is often limited or poorly contextualized in sports practice.The study employs a descriptive qualitative approach with purposive sampling techniques, involving 10-15 physics students with experience in recreational or competitive sports. Data were collected through semi-structured interviews to explore their views on the application of physics in sports, challenges in understanding sports-related physics concepts, and how physics can improve athletic performance.The findings indicate that most students recognize the importance of physics in sports. However, they feel that deeper physics understanding is insufficiently integrated into their physics curriculum. Some participants mentioned that the application of physics in sports could help prevent injuries and improve movement techniques. Despite this, many perceive physics as an abstract concept rather than something directly applicable to the sports world.This research provides insights into how students' perceptions of physics in sports can be enhanced and the need for more applicative and contextual teaching approaches. The findings are also expected to contribute to the development of more relevant and engaging physics teaching materials by integrating commonly encountered sports elements into everyday life.